ANALYSIS OF THE VALUE OF RELIGIOUS MODERATION IN LEARNING MODULE OF ISLAMIC RELIGIOUS EDUCATION AND CHARACTER - Fauzi Muharom (Profetika: Jurnal Studi Islam, 2023)
The study aims to analyze the value of religious moderation in module learning Islamic Religious Education and Character "Al-Hikmah" works Working Group for Elementary School Islamic Religious Education Teachers in District Wonogiri. Study this method study library research that uses books, written documents, and other relevant objects discussed as source research. As for object research used in the study, module learning Islamic Religious Education and Character "Al-Hikmah" Elementary School level grade 4 and grade 6. Research results show that modules learning Islamic Religious Education and Character "Al-Hikmah" in Elementary Schools in grades 4 and 6 contain material moderation religion, acceptable in a manner explicit nor a manner implicit. On the module learning Islamic Religious Education and Character "Al-Hikmah" class 4, there are 16 materials that contain payload moderation religious, and for module learning in grade 6, there are 14 containing material payload moderation religious.